Pedagogical Translanguaging in Language Education: Constructing Translanguaging Space to Reduce Cognitive Load in Support of Sustainable Development Goals (SDGs) - Putra, Harjuli Surya; Sugiharto, Setiono; Silva, Anna Marietta Da; Syahrizal, Trisnendri (Universitas Negeri Makassar, 2025)
This study aims to investigate how pedagogical translanguaging in language education constructs a translanguaging space to mediate and reduce extraneous cognitive load in EFL classrooms. Using a descriptive qualitative design, classroom observations and video-stimulated recall interviews were conducted with Indonesian university students. Data were analyzed through Multimodal Conversation Analysis combined with Interpretative Phenomenological Analysis. Results show that teacher-led pedagogical translanguaging connects multiple languages, addresses linguistic insecurity, and incorporates multimodal resources. These practices reduce cognitive load because they allow students to process new information by using their full linguistic repertoire, lowering stress and enhancing engagement. Constructing a translanguaging space fosters an inclusive environment, enabling students to participate more actively, retain content better, and develop metalinguistic awareness. The findings support the integration of pedagogical translanguaging into EFL teaching as a means to promote equity, linguistic diversity, and quality education, in alignment with Sustainable Development Goal 4.